Las Vegas in Singapore : Violence, Progress and the Crisis of Nationalist Modernity - Lee, Kah Wee (Book collections on Project MUSE., 2019)
Las Vegas in Singapore looks at the collision of the histories of Singapore and Las Vegas in the form of Marina Bay Sands, one of Singapore's two integrated resorts. The first history begins in colonial Singapore in the 1880s, when British administrators revised gambling laws in response to the political threat posed by Chinese-run gambling syndicates. Following the tracks of these punitive laws and practices, the book moves into the 1960s when the newly independent city-state created a national lottery while criminalizing both organized and petty gambling in the name of nation-building. The second history shifts the focus to corporate Las Vegas in the 1950s when digital technology and corporate management practices found each other on the casino floor. Tracing the emergence of the specialist casino designer, the book reveals how casino development evolved into a highly rationalized spatial template designed to maximize profits. Today an iconic landmark of Singapore, Marina Bay Sands is also an artifact of these two histories, an attempt by Singapore to normalize what was once criminalized in its nationalist history. Lee Kah-Wee argues that the historical project of the control of vice is also about the control of space and capital. The result is an uneven landscape where the legal and moral status of gambling is contingent on where it is located. As the current wave of casino expansion spreads across Asia, he warns that these developments should not be seen as liberalization but instead as a continuation of the project of concentrating power by modern states and corporations.